The Influence of Islamic Leadership and Remuneration on Organizational Citizenship Behaviour and Its Impact on Job Satisfaction at MItra Keluarga Husada Klaten General Hospital - Subiyanto, Totok; Aini, Qurratul (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Background: Job satisfaction problems that lead to a performance in improving hospital services' quality, which many hospital managers face today. Employees ask for high remuneration to enhance their performance, but this can reduce hospital income. Islamic leadership patterns can balance the demand for employee remuneration, which can provide an OCB culture and improve employee job satisfaction.Method: The study used a cross-sectional quantitative method using primary data obtained from questionnaires through google form and analyzed using smart PLS.Results and discussions: Based on shared questionnaires, there are 90 responses included in the inclusion criteria and retrieved data. Remuneration and Islamic leadership significantly influence OCB. OCB  has an impact on job satisfaction but is not significantConclusion: Islamic leadership and remuneration have a significant positive influence on OCB and job satisfaction Latar Belakang: Masalah kepuasan kerja yang mempengaruhi pada kinerja dalam meningkatkan mutu pelayanan rumah sakit, banyak dihadapi oleh pengelola rumah sakit saat ini. Karyawan meminta remunerasi yang tinggi untuk meningkatkan kinerja mereka, tetapi hal ini dapat mengurangi pendapatan rumah sakit. Pola kepemimpinan Islami dapat menyeimbangkan tuntutan remunerasi karyawan, yang dapat memberikan budaya OCB dan meningkatkan kepuasan kerja karyawan.Metode: Penelitian ini menggunakan metode kuantitatif cross sectional dengan menggunakan data primer yang diperoleh dari kuesioner melalui google form dan dianalisis menggunakan smart PLS.Hasil dan diskusi: Berdasarkan kuesioner yang dibagikan, ada 90 tanggapan yang termasuk dalam kriteria inklusi dan data yang diambil. Kombinasi antara remunerasi dan Islamic leadership berpengaruh signifikan terhadap OCB. OCB memberikan pengaruh signifikan terhadap kepuasan kerja. Kesimpulan: Islamic leadership dan remunerasi berpengaruh positif signifikan terhadap OCB dan kepuasan kerja